Conservation value of small reserves. Issue 1 (28th March 2019) - Volenec, Zoe M.; Dobson, Andrew P.
Abstract: The importance of large reserves has been long maintained in the scientific literature, often leading to dismissal of the conservation potential of small reserves. However, over half the global protected‐area inventory is composed of protected areas that are <100 ha, and the median size of added protected area is decreasing. Studies of the conservation value of small reserves and fragments of natural area are relatively uncommon in the literature. We reviewed SCOPUS and WOK for studies on small reserve and fragment contributions to biodiversity conservation and ecosystem services, and fifty‐eight taxon‐specific studies were included in the review. Small reserves harbored substantial portions (upward of 50%) of regional species diversity for many taxa (birds, plants, amphibians, and small mammals) and even some endemic, specialist bird species. Unfortunately, small reserves and fragments almost always harbored more generalist and exotic species than large reserves. Community composition depended on habitat quality, surrounding land use (agricultural vs. urban), and reserve and fragment size, which presents opportunities for management and improvement. Small reserves also provided ecosystem services, such as pollination and biological pest control, and cultural services, such as recreation and improved human health. Limitations associated with small reserves, such as extinction debt and support of area‐sensitive species, necessitate a complement of larger reserves. However, we argue that small reserves can make viable and significant contributions to conservation goals directly as habitat and indirectly by increasing landscape connectivity and quality to the benefit of large reserves. To effectively conserve biodiversity for future generations in landscapes fragmented by human development, small reserves and fragments must be included in conservation planning. Abstract : Article impact statement : Small reserves make meaningful contributions to biodiversity conservation and provisioning of ecosystem services. Abstract : Valor de Conservación de las Pequeñas Reservas Resumen: La importancia de las reservas muy extensas se ha mantenido durante mucho tiempo dentro de la literatura científica, lo que comúnmente lleva a la desestimación del potencial de conservación de las reservas pequeñas. Sin embargo, más de la mitad del inventario mundial de áreas protegidas está compuesto por zonas resguardadas con un tamaño menor a las 100 ha, y el tamaño promedio de área protegida añadida está disminuyendo. Los estudios sobre el valor de conservación de las reservas pequeñas y los fragmentos de área natural son relativamente poco comunes en la literatura. Revisamos estudios sobre las contribuciones de las reservas pequeñas y los fragmentos a la conservación de la biodiversidad y los servicios ambientales en SCOPUS y en WOK. Se incluyeron 58 estudios específicos de taxón en la revisión. Las reservas pequeñas albergaron porciones sustanciales (más del 50%) de diversidad de especies regionales para muchos taxones e incluso algunas especies de aves endémicas y especialistas. Desafortunadamente, las reservas pequeñas y los fragmentos casi siempre albergaron más especies exóticas y generalistas que las reservas grandes. La composición de la comunidad dependió de la calidad del hábitat, el uso de suelo (urbano versus agrícola) adyacente y el tamaño de la reserva o el fragmento, lo que presenta oportunidades de manejo y mejora. Las reservas pequeñas también proporcionaron servicios ambientales, como la polinización y el control biológico de plagas, y servicios culturales, como la recreación y una mejor salud humana. Las limitaciones asociadas con las reservas pequeñas, como la deuda de extinción y el respaldo a especies sensibles al área, requieren de un complemento de reservas más grandes. Sin embargo, argumentamos que las reservas pequeñas pueden tener contribuciones viables y significativas para las metas de conservación directamente como hábitat e indirectamente con el incremento de la conectividad y la calidad de paisajes para el beneficio de las reservas más grandes. Para conservar efectivamente a la biodiversidad para generaciones futuras en paisajes fragmentados por el desarrollo humano, se debe incluir a las reservas pequeñas y a los fragmentos en la planeación de la conservación. 摘要: 长期以来, 科学研究都在强调大型保护区的重要性, 这常常导致人们忽视了小型保护区的保护潜力。然而, 全球保护区列表中超过一半的保护区面积不足 100 公顷, 且新增保护区大小的中位数也在逐渐下降。文献中很少有关于小型保护区及破碎化的自然景观的保护价值的研究。因此, 我们综述了 SCOPUS 及 WOK 数据库的研究中, 小型保护区和破碎化的自然景观对生物多样性保护及生态系统服务的贡献, 其中包含了 58 项针对明确类群的研究。许多类群 (鸟类、植物、两栖类、小型哺乳动物), 甚至是特有的区域性鸟类物种多样性中, 很大一部分 (超过 50%) 都来自小型保护区。不幸的是, 小型保护区和自然景观碎片相比于大型保护区通常有更多的广布种和外来物种。群落组成依赖于生境质量、周围的土地利用类型 (农业或城市) 和保护区及碎片大小, 这为小型保护区的管理和提升提供了机会。小型保护区还提供了生态系统服务, 如传粉、生物害虫防治、文化服务 (休闲娱乐、改善人类健康) 等。而小型保护区存在的限制, 如灭绝债务、来自区域敏感物种的支持, 则需要大型保护区进行弥补。尽管如此, 我们认为小型保护区既可以提供栖息地, 又可以提高景观连接度和质量来支持大型保护区, 因而直接或间接地为保护目标作出了切实可行的重要贡献。为了有效地为子孙后代保护这些人类发展导致的破碎景观中的生物多样性, 保护规划必须涵盖小型保护区和自然景观碎片。【翻译: 胡怡思; 审校: 聂永刚】